2014
DOI: 10.1007/s11604-014-0326-9
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem lung features in drowning cases on computed tomography

Abstract: Postmortem CT images of drowning cases can be classified into three major types with a few exceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This study supports previous studies suggesting that pulmonary CT imaging evaluations should be performed at least 24 h after bronchoalveolar lavage for interpretation without lavage associated disturbances. The ground glass lung attenuation observed in the present study and a previous human study was considered to indicate aspiration of water, based on the lung changes described in a postmortem CT study after drowning in human medicine . The lung consolidation at the fluid‐infusion site likely represents replacement by fluid in the airways with less or no preserved visibility of vascular markings.…”
Section: Discussionmentioning
confidence: 94%
“…This study supports previous studies suggesting that pulmonary CT imaging evaluations should be performed at least 24 h after bronchoalveolar lavage for interpretation without lavage associated disturbances. The ground glass lung attenuation observed in the present study and a previous human study was considered to indicate aspiration of water, based on the lung changes described in a postmortem CT study after drowning in human medicine . The lung consolidation at the fluid‐infusion site likely represents replacement by fluid in the airways with less or no preserved visibility of vascular markings.…”
Section: Discussionmentioning
confidence: 94%
“…When an entire lung field of an infant is occupied by consolidation and/or ground-glass opacity in clinical practice, the physician will routinely predict diffuse infection, respiratory distress syndrome (surfactant deficiency), pulmonary oedema from a variety of causes or atelectasis. In post-mortem cases, post-mortem hypostasis and drowning may be additionally included in the differential diagnosis [13,14]. However, as a result of this study, this diagnostic process was inapplicable for infant PMCT.…”
Section: Discussionmentioning
confidence: 83%
“…According to previous studies, ground glass opacity (GGO) is found frequently on postmortem chest CT image in drowning. Usui et al [14] evaluated the features and further classified GGO into six types. However, GGO also has been described in other causes of death, especially cardiac death [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…One is pulmonary changes (ground glass opacity). Usui et al [14] evaluated the features of drowning postmortem chest CTs and classified these features into six types: two main types were ground glass opacities with thickened pulmonary interstitium, and a centrilobular distribution of illdefined nodules along the airways. However, they did not compare this finding with other causes of death as controls.…”
Section: Introductionmentioning
confidence: 99%